PERFORMANCE INVESTIGATION OF WIND TURBINES BASED ON DOUBLY FED INDUCTION GENERATORS WITH BACK-TO-BACK CONVERTER - Abdullah Muwafaq Alyousuf; Fatih Korkmaz (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ, 2023)
In the last decades, wind turbines have been extensively studied due to the increasing demand for renewable energy sources. Based on a very strong background of operational experience with wind turbine generators of varying sizes and the development of high-performance power electronics, these most recent wind turbine generators offer the requisite and enhanced performance for their safe integration into the power systems. In the past, wind turbine generators were simply connected to distribution networks; however, current projects and wind turbine generators sizes require a direct connection to the transmission system level through a project-specific substation. Due to these developments, an integrated strategy is needed to maximize the allocation of control responsibilities between substation control and wind turbine control. Dual-Fed Induction Generator (DFIG) systems can be used in many ways to make complex solutions. In this paper, the design and control of DFIG systems are presented to improve WT operating performance in different cases. Given the strong association between converter control strategies and working conditions, it is important to better understand to demonstrates the importance of developing an appropriate modelling approach. The key findings are discussed, and recommendations are provided for future research in this paper.